Dynamic behavior of geopolymer stabilized kaolin clay under long-term cyclic loading - Gupta S.; Kumar S. (My University, 2025)
Geopolymer has emerged as an alternate cementitious material with a low carbon footprint, as they improve the engineering properties of soft soil without causing a detrimental effect on the environment. This study focuses on developing a combination of geopolymer materials that can fully replace the utilization of traditional binders to stabilize soft soil foundations in geotechnical engineering. Soft kaolin clay was stabilized using ground-granulated blast furnace slag (S) and dolomite (D) as a precursor (P) with combined content of 20% and NaOH: Na2SiO3 ratio of 25:75 as a liquid alkali activator (L) in the geopolymerization process. A series of Unconfined Compressive Strength (UCS) tests were conducted to analyze the influence of various parameters, such as the ratio of S and D, water content of kaolin clay, curing period, and L/P ratio, to select the optimum mix proportions based on strength improvement. This paper also discusses the behavior of geopolymer-stabilized kaolin clay under long-term cyclic loading in stress-controlled conditions. The effect of the S:D ratio, cyclic stress ratio (CSR), curing time, frequency, and confining pressure (CP) on the dynamic shear modulus (G), damping ratio (λ), and degradation index (G/Gmax) were analyzed. The results indicate that the S:D ratio of 16:4 with an L/P ratio of 1, NaOH: Na2SiO3 ratio of 25:75, and water content of liquid limit (LL) cured for 28 days gives the highest UCS value of 1.47 MPa. The initial dynamic shear modulus (Gmax) increases by 60% as the S:D ratio changes from 20:0 to 16:4. The cyclic performance of geopolymer-stabilized kaolin clay in terms of accumulative strain as a function of the number of loading cycles was also enhanced. The findings of the study provide guidance to a better understanding of the long-term dynamic behavior and application of geopolymer-stabilized kaolin clay as a greener approach to ground improvement. © 2023 Elsevier Ltd